Efektivitas Media Visual Dalam Dakwah Islam: Studi Pada Kegiatan Tutorial Pendidikan Agama Islam di UPI - Nelsya Winanda; Nafisa Maliqa Maulana; Cucu Surahman (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to see the extent to which visual media is effective in supporting Islamic da'wah activities through Islamic Religious Education (PAI) tutorials at the Indonesian University of Education (UPI). This is because visual media is currently an important part of educational and da'wah communication, especially among the digital generation who are more responsive to visual information than conventional approaches. The approach used is a mixed method, namely a combination of quantitative methods with data collection through questionnaires and qualitative methods through interviews and observations. The results of the study show that visual media such as learning videos, social media content, and da'wah animations play a significant role in increasing students' understanding and acceptance of religious material. Digital platforms such as TikTok are popular media used by students to access da'wah content. The main factors that influence the effectiveness of visual media are the quality of the design and appearance of the media and the relevance of the content to the da'wah material. These findings indicate that visual media not only facilitate the delivery of da'wah messages, but also contribute to shaping students' religious attitudes. This study provides recommendations for the development of more contextual and communicative da'wah media to improve the quality of PAI learning in higher education.